How to negotiate with the Chinese? - Svetličič, Marjan (Mednarodno inovativno poslovanje, 2022)
The objective of this article is to enhance bargaining competences of managers negotiating with Chinese partners. It was achieved first by evaluating general characteristics of cross-cultural negotiations, followed by specifics of negotiating with the Chinese partners. Based on the mistakes managers do in negotiating with Chinese partners, special attention was directed to: prevailing values, communication specifics, dualism in negotiating with foreigners (ying-yang), the importance of keeping up one’s respect, relationships (guanxi) and differences in terms of time, organization of the meetings, and finally, their view on contracts. Mastering such specifics and avoiding too frequently rooted stereotypes are preconditions for success on the Chinese market
Keywords: kompetence; kulturne razlike; menedžerji; Poslovna pogajanja